PEMENUHAN INVESTASI DAERAH DAN TINGKAT PENDIDIKAN TERHADAP PERTUMBUHAN EKONOMI - Imammudin, Yusuf; Satriatama, Keifan Galuh; Anjaska, Reza (Jurnal Edukasi Ekonomi, 2023)
This research aims to analyze the influence of investment in an area with a level of education on economic growth in the vulnerable city of Bandar Lampung from 2019 to 2023. According to data collected at BPS Lampung Province 2023, the economic growth of the city of Bandar Lampung from 2019 to 2023 is moving fluctuatingly, which in this case is influenced by several factors, including investment in the workforce and the level of education in the city of Bandar Lampung. The data used in this research uses vulnerable secondary data from 2019 to 2023 using documentation methods obtained from the BPS of Bandar Lampung City province. By using multiple linear regression analysis. The results of research referring to investment fulfillment based on linear regression test results show results on investment variables (0.0230.05) along with education level (0.0010.05) which have a positive effect on the economic growth of the city of Bandar Lampung. And based on the simultaneous level of Bandar Lampung City at 99.8%, which refers to the welfare index that comes from fulfilling investment and education levels in Bandar Lampung City.